2014
DOI: 10.1111/tpj.12670
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis RAV1 transcription factor, phosphorylated by SnRK2 kinases, regulates the expression of ABI3,ABI4, and ABI5 during seed germination and early seedling development

Abstract: These three authors contributed equally to this work. SUMMARYThe phytohormone abscisic acid (ABA) modulates a number of processes during plant growth and development. In this study, the molecular mechanism of Arabidopsis RAV (Related to ABI3/VP1) transcription factor RAV1 involving ABA signaling was investigated. RAV1-underexpressing lines were more sensitive to ABA than wild-type plants during seed germination and early seedling development, whereas RAV1-overexpressing lines showed strong ABA-insensitive phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(156 citation statements)
references
References 85 publications
(171 reference statements)
5
146
2
3
Order By: Relevance
“…Expression profiles for each gene of single stages of the transition matched with known expression profiles (Ding et al, 2006;Tepperman et al, 2006;Hammani et al, 2011;Narsai et al, 2011;Feng et al, 2014), validating the data set. Expression data across the seven developmental stages displayed high reproducibility.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Expression profiles for each gene of single stages of the transition matched with known expression profiles (Ding et al, 2006;Tepperman et al, 2006;Hammani et al, 2011;Narsai et al, 2011;Feng et al, 2014), validating the data set. Expression data across the seven developmental stages displayed high reproducibility.…”
Section: Discussionsupporting
confidence: 56%
“…Expression data are hosted in the National Center for Biotechnology Information Gene Expression Omnibus database (http://www.ncbi.nlm.nih.gov/ geo/query/acc.cgi?token=onyxsyycjtaxxux&acc=GSE65394). Validation of the seed-to-seedling transcriptome data set was performed by comparison with previously published expression patterns of genes known to be differentially expressed across seed-to-seedling developmental stages (Supplemental Table S1; Ding et al, 2006;Tepperman et al, 2006;Hammani et al, 2011;Narsai et al, 2011;Feng et al, 2014).…”
Section: Microarray Hybridizationmentioning
confidence: 99%
“…In the ABA signaling pathway, transcription factor RAV1 represses the expression of ABI3, ABI4, and ABI5. Protein kinases SnRK2s are activated by the ABA signal and then phosphorylate RAV1, which removes RAV1 repression on ABI5 transcription (Feng et al, 2014). Here, we demonstrated that low-K + stress triggers a rapid phosphorylation of ARF2 ( Figure 9B).…”
Section: Phosphorylation Is An Important Regulatory Mechanism For Arfmentioning
confidence: 53%
“…4 D and E). ABA-activated SnRK2s phosphorylate RAV1 (30), which positively regulates leaf senescence in Arabidopsis (31). According to the Arabidopsis eFP browser, expression of ORE1, ORS1, and AtNAP is enhanced by ABA (Fig.…”
Section: Phosphorylation Of Abfs By Snrk2s Facilitates Aba-induced Sag12mentioning
confidence: 99%